PERKERASAN JALAN MENUJU ECO CAMP MANGUNKARSA PANTAI GRIGAK KELURAHAN GIRIKERTO,KAPANEWON PANGGANG,KABUPATEN GUNUNGKIDUL - John Tri Hatmoko; Dinar Gumilang Jati (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Mangunkarsa Ecocamp is located on Grigak Beach, the village of Karang, Gunungkidul egency. It was built as the conservation area. However, there is almost no connection between Ecocamp and Karang village ; then it is required to build the roadway connecting those two locations. To meet the requirement, this public service programs attempted to provide the connecting roadway of those two locations. The roadway was designed with the length of 2,00 km and 3,00 meters width, and the surface course was designed as sand sheet pavement. The budget for material was supported by the government, and it was also provided by the local society for project execution . There were three steps to complete the program. The first step was location field-survey to make sure the site conditions, followed by soil sampling for subgrade design. The second was to perform laboratory experiment to verify physical and mechanical properties of soil, and it was followed with design the pavement , and the last was to execute the project. The laboratory experiment was done according to the standard, the pavement design was done according to the guidance issued by the Ministry of PUPR, and the project execution was done according to the basic standard. The results showed that the soil was met the requirement as subgrade, the thickness of the pavement was obtained 6 cm thick. The project execution was finished within 10 days